Split-Doa10: A Naturally Split Polytopic Eukaryotic Membrane Protein Generated by Fission of a Nuclear Gene - Stuerner, Elisabeth; Kuraku, Shigehiro; Hochstrasser, Mark; Kreft, Stefan G. (PLOS ONE, 2012)
Large polytopic membrane proteins often derive from duplication and fusion of genes for smaller proteins. The reverse process, splitting of a membrane protein by gene fission, is rare and has been studied mainly with artificially split proteins. Fragments of a split membrane protein may associate and reconstitute the function of the larger protein. Most examples of naturally split membrane proteins are from bacteria or eukaryotic organelles, and their exact history is usually poorly understood. Here, we describe a nuclear-encoded split membrane protein, split-Doa10, in the yeast Kluyveromyces lactis. In most species, Doa10 is encoded as a single polypeptide with 12–16 transmembrane helices (TMs), but split-KlDoa10 is encoded as two fragments, with the split occurring between TM2 and TM3. The two fragments assemble into an active ubiquitin-protein ligase. The K. lactis DOA10 locus has two ORFs separated by a 508-bp intervening sequence (IVS). A promoter within the IVS drives expression of the C-terminal KlDoa10 fragment. At least four additional Kluyveromyces species contain an IVS in the DOA10 locus, in contrast to even closely related genera, allowing dating of the fission event to the base of the genus. The upstream Kluyveromyces Doa10 fragment with its N-terminal RING-CH and two TMs resembles many metazoan MARCH (Membrane-Associated RING-CH) and related viral RING-CH proteins, suggesting that gene splitting may have contributed to MARCH enzyme diversification. Split-Doa10 is the first unequivocal case of a split membrane protein where fission occurred in a nuclear-encoded gene. Such a split may allow divergent functions for the individual protein segments.